Fermented Jussara: Evaluation of Nanostructure Formation, Bioaccessibility, and Antioxidant Activity - Giaconia, Michele Amendoeira; Ramos, Sergiana dos Passos; Fratelli, Camilly; Assis, Marcelo; Mazzo, Tatiana Martelli; Longo, Elson; de Rosso, Veridiana Vera; Braga, Anna Rafaela Cavalcante (Frontiers in Bioengineering and Biotechnology, 2022)
Among the species of plants present in the Atlantic Forest, the jussara (Euterpe edulis Mart.) stands out for the contents of bioactive compounds present in its composition. Fermentation processes can be essential in converting bioproducts and bioactive compounds, improving their biological properties. In addition, the improvement of procedures for the maintenance of the features of bioactive compounds has been a research focus in recent years, and the nanotechnology features that can potentially solve this issue have been highlighted among the most reviewed paths. The present work focused on tailoring nanostructures applying polyethylene oxide, assembling fermented jussara pulp nanofibers, and assessing their characteristics. The results revealed the formation of fermented jussara nanofibers with a diameter of 101.2 ± 26.2 nm. Also, the obtained results allow us to state that it is possible to maintain or even increase the antioxidant activity of anthocyanins and their metabolites after fermentation processes.